INOVASI TEKNOLOGI UNTUK PELAYANAN MASYARAKAT: SOLUSI DIGITAL PENCATATAN PENDUDUK DI ERA 4.0 - Rizaldi Putra; Memet Sanjaya; Lambok Rommy Sulaeman; Chowal Jundy Kumoro; Deni Utama; Kinanti Dwi Adelia; Tessalonika Audry Polnaya (Bajang Institute, 2025)
Mega Regency Housing, particularly RW 016, still uses a manual resident registration system, which causes administrative issues such as delays in services, data inaccuracy, and difficulties in tracking important events like deaths, relocations, and elections. This study aims to identify the problems in the current system and design an innovative digital solution based on information technology. A descriptive qualitative approach was used through in-depth interviews, observations, documentation, and focus group discussions. The findings indicate that a digital system has high potential to improve the efficiency and accuracy of public services at the RW level. However, successful implementation depends heavily on human resource readiness, infrastructure support, and policy backing. Therefore, digitalization of resident registration at the RW level must be carried out gradually, inclusively, and sustainably